If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x(-3x + -1) = 16 Reorder the terms: -5x(-1 + -3x) = 16 (-1 * -5x + -3x * -5x) = 16 (5x + 15x2) = 16 Solving 5x + 15x2 = 16 Solving for variable 'x'. Reorder the terms: -16 + 5x + 15x2 = 16 + -16 Combine like terms: 16 + -16 = 0 -16 + 5x + 15x2 = 0 Begin completing the square. Divide all terms by 15 the coefficient of the squared term: Divide each side by '15'. -1.066666667 + 0.3333333333x + x2 = 0 Move the constant term to the right: Add '1.066666667' to each side of the equation. -1.066666667 + 0.3333333333x + 1.066666667 + x2 = 0 + 1.066666667 Reorder the terms: -1.066666667 + 1.066666667 + 0.3333333333x + x2 = 0 + 1.066666667 Combine like terms: -1.066666667 + 1.066666667 = 0.000000000 0.000000000 + 0.3333333333x + x2 = 0 + 1.066666667 0.3333333333x + x2 = 0 + 1.066666667 Combine like terms: 0 + 1.066666667 = 1.066666667 0.3333333333x + x2 = 1.066666667 The x term is 0.3333333333x. Take half its coefficient (0.1666666667). Square it (0.02777777779) and add it to both sides. Add '0.02777777779' to each side of the equation. 0.3333333333x + 0.02777777779 + x2 = 1.066666667 + 0.02777777779 Reorder the terms: 0.02777777779 + 0.3333333333x + x2 = 1.066666667 + 0.02777777779 Combine like terms: 1.066666667 + 0.02777777779 = 1.09444444479 0.02777777779 + 0.3333333333x + x2 = 1.09444444479 Factor a perfect square on the left side: (x + 0.1666666667)(x + 0.1666666667) = 1.09444444479 Calculate the square root of the right side: 1.046156989 Break this problem into two subproblems by setting (x + 0.1666666667) equal to 1.046156989 and -1.046156989.Subproblem 1
x + 0.1666666667 = 1.046156989 Simplifying x + 0.1666666667 = 1.046156989 Reorder the terms: 0.1666666667 + x = 1.046156989 Solving 0.1666666667 + x = 1.046156989 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.1666666667' to each side of the equation. 0.1666666667 + -0.1666666667 + x = 1.046156989 + -0.1666666667 Combine like terms: 0.1666666667 + -0.1666666667 = 0.0000000000 0.0000000000 + x = 1.046156989 + -0.1666666667 x = 1.046156989 + -0.1666666667 Combine like terms: 1.046156989 + -0.1666666667 = 0.8794903223 x = 0.8794903223 Simplifying x = 0.8794903223Subproblem 2
x + 0.1666666667 = -1.046156989 Simplifying x + 0.1666666667 = -1.046156989 Reorder the terms: 0.1666666667 + x = -1.046156989 Solving 0.1666666667 + x = -1.046156989 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.1666666667' to each side of the equation. 0.1666666667 + -0.1666666667 + x = -1.046156989 + -0.1666666667 Combine like terms: 0.1666666667 + -0.1666666667 = 0.0000000000 0.0000000000 + x = -1.046156989 + -0.1666666667 x = -1.046156989 + -0.1666666667 Combine like terms: -1.046156989 + -0.1666666667 = -1.2128236557 x = -1.2128236557 Simplifying x = -1.2128236557Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.8794903223, -1.2128236557}
| (3x+7)(2x+1)= | | p/7-3=-10 | | -5(-3-1)=16 | | 37=11x+70 | | 2.5+5.04=8.5-0.6 | | -16=-5w+3(w-6) | | -3(w-6)+7w+1= | | -12m-(-12)=12 | | 10/q=9/5 | | 20=-3x+32 | | 3/11=9/a | | 9=h/4+9 | | 2(3x+6)4X-3=59 | | X=40X-240 | | 5x(4x^2+x+8)= | | 0=-16t^2+48 | | b+17=-22 | | 6/11=x/4 | | h=-16t^2+48 | | 3500+250x=17615+550x | | 5w-1=21+3w | | 18n(2)-50=0 | | 10p+12q=56 | | 1x-15=15 | | ln(r+4)=ln(5s+2) | | 5-2m=13m | | -2(x-4)=-14 | | 8-(-10)=74 | | m/-910 | | -2(x-4)=-15 | | x^2-3x-1=6 | | 4(x-12)=22 |